Improving Students Reading Comprehension through Question And Answer Relationship and Timed Repeated Reading (QAR-TIRRE) Strategy at Grade Nine Students of SMPN 4 Jember - Budi, Avilanofa Bagus (Journal of English in Academic and Professional Communication, 2020)
There were at least two crucial problems faced by the students of SMPN 4 Jember in reading class. The first problem was the teachers technique that was not able to improve students reading comprehension. The second problem was students inability in answering different level of questions. In other words, the students score on reading comprehension were poor. To solve the two problems, the researcher conducted a classroom action research by using Question  And Answer Relationship strategy in improving students reading comprehension. The findings showed that QAR-TIRRE strategy improved students reading comprehension. In the first cycle, the number of students who got the score greater or equal to 70 was only 19 students out of 38 students or 50%. It had not fulfilled the criterion of success yet. But, in the second cycle, the students who got the score greater or equal to 70 were 27 out of 38 students or 71, 05%. In addition, the result of the students participation increased from 05,26% in cycle I to 10,53% in cycle II. It fulfilled the criterion of the success in terms of score improvement. Based on the result, the researcher claimed that the QAR-TIRRE strategy improved students reading comprehension. Hopefully, it could be significant input for the teacher and other researchers to teach and conduct research especially related to the teaching of reading.